A Facile Reduction Method for Roll‐to‐Roll Production of High Performance Graphene‐Based Transparent Conductive Films. Issue 9 (2nd January 2017) - Ning, Jing; Hao, Long; Jin, Meihua; Qiu, Xiongying; Shen, Yudi; Liang, Jiaxu; Zhang, Xinghao; Wang, Bin; Li, Xianglong; Zhi, Linjie
Abstract : A facile roll‐to‐roll method is developed for fabricating reduced graphene oxide (rGO)‐based flexible transparent conductive films. A Sn 2+ /ethanol reduction system and a rationally designed fast coating–drying–washing technique are proven to be highly efficient for low‐cost continuous production of large‐area rGO films and patterned rGO films, extremely beneficial toward the manufacture of flexible photoelectronic devices.